ANALISIS NILAI TAMBAH USAHA PENGOLAHAN IKAN MANYUNG ASAP DI KABUPATEN DEMAK - Awami, Shofia Nur; Nurjayanti, Eka Dewi; Subekti, Endah (Universitas Medan Area, 2019)
Traditional methods of processing fishery products are fumigation. Processing of fishery products has objectives including increasing added value. This research aimed to determine: 1). added value of smoked manyung fish processing business, 2). the level of feasibility and the profit of smoked manyung fish processing business, and 3). the factors that influenced added value of smoked manyung fish processing business. This research covered analysis methods several including, the added value analysis according Hayami, et all (1987), the profit and feasibility analysis, and multiple linear regression analysis. The research showed that the added value of processing smoked manyung fish business is Rp. 4,042 per kilogram. The average total revenue for smoked manyung fish processing per production cycle of Rp.2,773,000, and average profit of Rp.251,908. Furthermore, RC ratio value of 1.154, units BEP of processing smoked manyung fish amount to 16,442 kilogram and the revenue value BEP is Rp.358,604. Added value of processed smoked manyung fish in Demak District were influenced by several factors including; the amount of labor, the amount of raw materials, the processor?s age, and output prices.